Creative thinking strategies in academic debate among university students - Sabriadi, Ririn; Azis, Azis; Jufri, Jufri; Juanda, Juanda (Edelweiss Applied Science and Technology, 2026)
This study aims to examine creative thinking strategies in academic debate among university students by identifying the representation of convergent thinking, divergent thinking, and lateral creative thinking in the Indonesian Student Debate Competition. The study employed a qualitative descriptive design. The data were obtained from debate recordings available on the YouTube platform and collected through observation and transcription techniques. The data were analyzed using an interactive model consisting of data condensation, data display, and conclusion drawing and verification. The findings reveal that divergent thinking is the most dominant strategy, reflected in students’ ability to explore broad ideas, shift perspectives, and build associations across issues. Convergent thinking supports the organization of ideas into logical, coherent, and decision-oriented arguments. Lateral creative thinking appears less frequently but contributes to challenging dominant assumptions, reframing issues, and producing non-linear perspectives. Creative thinking in academic debate functions as a strategic process that strengthens argument quality and discourse innovation. The findings provide insights for developing debate pedagogy and language learning practices in higher education.